Dinámica familiar y desarrollo psicosocial en estudiantes de educación primaria - Romero de Harb, Dayalí Pastora (2018)
The relevance of the family in society is indisputable, the parents are directly responsible for the childhood formation, preparing them for life, independent and productive for society. In that context, we found out to determine the relationship between Family Dynamics and Psychosocial Development of Primary Education students of a Private Educational Institution by Punto Fijo, Falcón State - Venezuela. The investigation research was descriptive correlational, with non-experimental design, transactional field. The sampling was non-probabilistic, intentional type, made up of 28 children of 1st grade and 24 children of 2nd grade from 6 to 8 years old, without sensory, cognitive or social disorders. Psychosocial development was assessed through a structured observation guide and family dynamics with a questionnaire assessed family ties, contacts, processes, pillars and family context. The results, when applying Pearson's correlation index, confirmed the hypothesis that Family Dynamics affects the Psychosocial Development of children, but in a weak way (0.09); that is, for an optimal child development to take place, there must be a familiar and social environment that favors it. It is concluded that family dynamics in its dimensions: family ties, contacts, processes, pillars and family context supports the approach of family members, stimulating psychosocial development through interaction and self-control behaviors in certain situations.